Comparative Study of UV Spectrophotometric Methods for the Determination of Ethamsylate in Bulk and Pharmaceutical Formulations - Nageshwara Rao, R.; Nagaraju, P.; Srinivasulu, C.; Jitendra Kumar, P.; Suresh, V.; Sireesha, D. (Asian Journal of Chemistry, 2016)
Two simple, sensitive and reproducible UV spectrophotometric methods (A and B) for the determination of ethamsylate (EMS) in bulk samples and pharmaceutical formulations are described. EMS was taken in methanol for method A and in 0.1 N HCl for method B. The maximum absorbance was observed at 302 nm for method A and 302 nm for method B. Regression analysis of Beer’s law plots showed good concentration ranges 2–10 μg/mL for method A and 5–15 μg/mL for method B respectively. There is no interference from any common pharmaceutical excipients.